A Fuzzing Tool Based on Automated Grammar Detection - Jia Song; Jim Alves-Foss (Software)
Software testing is an important step in the software development life cycle to ensure the quality and security of software. Fuzzing is a security testing technique that finds vulnerabilities automatically without accessing the source code. We built a fuzzer, called JIMA-Fuzzing, which is an effective fuzzing tool that utilizes grammar detected from sample input. Based on the detected grammar, JIMA-Fuzzing selects a portion of the valid user input and fuzzes that portion. For example, the tool may greatly increase the size of the input, truncate the input, replace numeric values with new values, replace words with numbers, etc. This paper discusses how JIMA-Fuzzing works and shows the evaluation results after testing against the DARPA Cyber Grand Challenge (CGC) dataset. JIMA-Fuzzing is capable of extracting grammar from sample input files, meaning that it does not require access to the source code to generate effective fuzzing files. This feature allows it to work with proprietary or non-open-source programs and significantly reduces the effort needed from human testers. In addition, compared to fuzzing tools guided with symbolic execution or taint analysis, JIMA-Fuzzing takes much less computing power and time to analyze sample input and generate fuzzing files. However, the limitation is that JIMA-Fuzzing relies on good sample inputs and works primarily on programs that require user interaction/input.